A Optimizing IoT-Based Real – Time Monitoring Systems for Personnel Conducting Jungle Patrols : A Case Study of Indonesian Army - Dodo Irmanto; Dekki Widiatmoko; Kasiyanto (International Research & Development for Human Beings (IRDH), 2025)
This study aims to explore the application of an Internet of Things (IoT)-based monitoring system in jungle warfare, focusing on the Indonesian Army. Through a methodological approach that combines the development of an IoTbased communication system prototype, this study identifies the challenges faced in real-time communication in a jungle environment. Key findings suggest that the use of advanced sensors and communication protocols such as LoRa (Long Range) can provide real-time information needed for fast and accurate decision-making, while minimizing the risk of fatigue and accidents that can occur during patrols. These findings imply that adopting an IoT-based communication system can significantly improve the effectiveness of military operations by the Indonesian Army in challenging jungle environments. This study also provides recommendations for further development of military communication infrastructure with real-time data delivery.